2011
DOI: 10.1108/09604521111113438
|View full text |Cite
|
Sign up to set email alerts
|

Generating positive word‐of‐mouth in the service experience

Abstract: Purpose -This paper seeks to investigate the effects of relationship benefits on relationship quality and aspects of service quality, namely technical and functional quality, and the subsequent influence on word-of-mouth behavior. Design/methodology/approach -The paper reports results from a structural equation model that utilizes data from 591 consumers across a range of services. Findings -The findings highlight the important role of relationship benefits in driving customer perceptions of technical, functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
129
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(143 citation statements)
references
References 66 publications
(106 reference statements)
7
129
1
6
Order By: Relevance
“…Despite pertinent studies acknowledge several employee-based determinants of customers' WOM (e.g. Wang, 2009;Ng, David, & Dagger, 2011), scarce evidence exists on whether transaction-specific outcomes from deviant exchanges affect customers' advocacy for the organization's brand. Encounter satisfaction is expected to enhance customers' WOM for the organization, as positive input from a service exchange can trigger favourable customer reactions (De Matos & Rossi, 2008).…”
Section: R2: Customer's Positive Affective State Is Expected To Have mentioning
confidence: 99%
“…Despite pertinent studies acknowledge several employee-based determinants of customers' WOM (e.g. Wang, 2009;Ng, David, & Dagger, 2011), scarce evidence exists on whether transaction-specific outcomes from deviant exchanges affect customers' advocacy for the organization's brand. Encounter satisfaction is expected to enhance customers' WOM for the organization, as positive input from a service exchange can trigger favourable customer reactions (De Matos & Rossi, 2008).…”
Section: R2: Customer's Positive Affective State Is Expected To Have mentioning
confidence: 99%
“…The relationship quality has three main components: satisfaction, trust, and commitment (Hennig-Thurau et al, 2002). Several studies have demonstrated that WOM is positively influenced by the relationship quality or some of its components, i.e., commitment, satisfaction, or trust (e.g., Brown et al, 2005;Macintosh, 2007;Hennig-Thurau et al, 2002;Ng, David, and Dagger, 2011).…”
Section: Antecedents Of Cebmentioning
confidence: 99%
“…The research area was at Pondicherry, a heritage coastal town in India. Studies for rural lodging sites such as Litvin, Goldsmith, & Pan, (2008) ;Ng, David, & Dagger, (2011) revealed that accommodation services were a very important intangible feature. The purchase process was inherently risky, because customers could not evaluate the services before check in.…”
Section: Literature Reviewmentioning
confidence: 99%